PEMBERDAYAAN IBU BALITA UNTUK MENINGKATKAN KESEHATAN ANAK MELALUI EDUKASI CEGAH DIARE DAN DEMONSTRASI PENDAMPING MAKANAN TAMBAHAN (PMT) BERBASIS PANGAN LOKAL - Qurrota 'Aini, Tazqia; Hanatha Pasha, Yessinia; Marlita Primastuti, Amanda; Lailatul Rochmah, Fani; Salsabila, Sania; Dewantika Santoso Putri, Aisyah; Yumna Nurul Ismah, Adinda; Puspitasari, Cindy; Arfiani, Sinta; Berliana Mulazamah, Nandini; Rokhmah, Dewi (Universitas Padjadjaran, 2025)
Diarrhea is a disease that is ranked second as the cause of death among children under five in the world. One of the important impacts of diarrhea in toddlers is related to malnutrition and growth failure, specifically stunting. Prolonged diarrhea can cause a decrease in nutritional status, especially in children under two years of age. Diarrhea prevention interventions are carried out through empowerment programs involving educational and coercive activities using the Participatory Rural Appraisal (PRA) method. PRA is an empowerment approach and technique that involves the community during program planning, implementation, monitoring, and evaluation activities. The material in the empowerment program is related to diarrhea, including the definition of diarrhea, the causes of diarrhea, and how to prevent diarrhea. This material is listed in the Cerdik Module, which includes menus with local ingredients. The empowerment program consists of two activities, namely diarrhea prevention education carried out by diarrhea care cadres and locally-based Supplemental Food Complementary Demonstration (PMT) activities. The activity was attended by 24 participants, namely mothers with children under five. Based on the results, it is known that the pre-test and post-test showed an increase in knowledge by 5.4%, as evidenced by the average pre-test score of 7.3 and the average post-test score of 7.7. Cooperation is needed between the government, community, and stakeholders related to diarrhea prevention efforts so that a diarrhea-free Sabrang Village can be realized. Diare merupakan penyakit dengan peringkat kedua sebagai penyebab kematian balita di dunia. Salah satu dampak penting diare pada balita adalah berkaitan dengan malnutrisi dan kegagalan pertumbuhan stunting. Diare yang berkepanjangan dapat menyebabkan penurunan status gizi, terutama pada anak di bawah usia dua tahun. Intervensi pencegahan diare dilakukan melalui program pemberdayaan melalui kegiatan edukasi dan demonstrasi dilakukan dengan metode Participatory Rural Appraisal (PRA). PRA merupakan pendekatan dan teknik pemberdayaan yang melibatkan masyarakat selama kegiatan perencanaan, pelaksanaan, pemantauan, dan evaluasi program. Materi dalam program pemberdayaan berkaitan dengan diare, diantaranya definisi diare, penyebab diare, hingga cara pencegahan diare. Materi tersebut tercantum dalam Modul Cerdik yang di dalamnya terdapat menu-menu dengan bahan lokal. Program pemberdayaan terdiri dari dua kegiatan yakni edukasi cegah diare yang dilakukan oleh kader peduli diare dan kegiatan Demonstrasi Pendamping Makanan Tambahan (PMT) berbahan dasar lokal. Kegiatan diikuti oleh 24 sasaran yakni ibu-ibu dengan anak yang memiliki balita. Berdasarkan hasil pre-test dan post-test diketahui terjadi peningkatan pengetahuan sebesar 5,4% dibuktikan dengan rata-rata skor pre-test sebesar 7,3 dan rata-rata skor post-test sebesar 7,7. Diperlukan kerjasama antara pemerintah, masyarakat, dan pemangku kepentingan yang berkaitan dengan upaya pencegahan diare sehingga dapat mewujudkan Desa Sabrang yang bebas diare.